Proyecto de creación de un bowling center en la ciudad de Milagro - Aviles, Miguel (2010)
The Project realize an analysis the Bowling Center principal characteristic in Milagro City, also realized a study on the market for identify important aspect the production and demand, also realized a finance and economic analysis for demonstrate that yes or no is rental and plan the strategies for establishment the business and have a good result on de market, realized a camp investigation with which was confirmation the enterprise’s number that realize the same business, construction and technology in the same city. For make real this project must finance the 40% with a credit that give for a bank and the 60% is for the shareholder’s contribution, in the moment that realize a feasibility analysis in the project estimate a VAN $300,666.75 and a TIR 25.48% with which affirm that the business is very rental.